A review of composite product data interoperability and product life-cycle management challenges in the composites industry. (2nd October 2017) - McMillan, Alison J.; Swindells, Norman; Archer, Edward; McIlhagger, Alistair; Sung, Anna; Leong, Kelvin; Jones, Rhys
Abstract: A review of composite product data interoperability and product life-cycle management challenges is presented, which addresses "Product Life-cycle Management", developments in materials. The urgent need for this is illustrated by the life-cycle management issues faced in modern military aircraft, where in-service failure of composite parts is a problem, not just in terms of engineering understanding, but also in terms of the process for managing and maintaining the fleet. A demonstration of the use of ISO 10303-235 for a range of through-life composite product data is reported. The standardization of the digital representation of data can help businesses to automate data processing. With the development of new materials, the requirements for data information models for materials properties are evolving, and standardization drives transparency, improves the efficiency of data analysis, and enhances data accuracy. Current developments in Information Technology, such as big data analytics methodologies, have the potential to be highly transformative. Abstract :